2013
DOI: 10.1039/c3sc51813b
|View full text |Cite
|
Sign up to set email alerts
|

Naphthalimide trifluoroacetyl acetonate: a hydrazine-selective chemodosimetric sensor

Abstract: Naphthalimide trifl uoroacetyl acetonate: a hydrazine-selective chemodosimetric sensorA trifl uoroacetyl acetonate naphthalimide derivative was synthesized in good yield and reacts selectively with hydrazine to give a fi ve-membered ring. This leads to OFF-ON fl uorescence with a maximum intensity at 501 nm as well as easily discernible color changes. As featured in:See Jong Seung Kim and Jonathan L. Sessler et al., Chem. Sci., 2013, 4 The trifluoroacetyl acetonate naphthalimide derivative 1 has been synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(68 citation statements)
references
References 30 publications
1
66
0
1
Order By: Relevance
“…It can hence be concluded that NTPE-DCV has a wide working pH range of 3-10 for hydrazine detection, which shows general suitability and better tolerance to acidic or basic conditions compared to previous reports. [42][43][44] The same trend is also observed for TPE-DCV and MTPE-DCV. …”
Section: Hydrazine Detection In Solutionsupporting
confidence: 81%
“…It can hence be concluded that NTPE-DCV has a wide working pH range of 3-10 for hydrazine detection, which shows general suitability and better tolerance to acidic or basic conditions compared to previous reports. [42][43][44] The same trend is also observed for TPE-DCV and MTPE-DCV. …”
Section: Hydrazine Detection In Solutionsupporting
confidence: 81%
“…Hervorzuheben ist auch der selektive Nachweis von Hydrazin (85), der auf der Cyclisierungsreaktion von (84) und (85) zu dem stark fluoreszierenden Naphthalimid (86) beruht (Abbildung 45) 127…”
Section: Organische Farbstoffeunclassified
“…A possible interaction between probe CF and N 2 H 4 is also suitable for the similar phenomenon in the fluorescence titration plot of other N 2 H 4 probes [42].…”
Section: The Proposed Reaction Mechanismmentioning
confidence: 98%